Pengaruh Rasio Likuiditas Current Ratio dan Quick Ratio Terhadap Kinerja Keuangan (ROA) pada PT. GarudaFood Putra Putri Jaya Tbk - Panjaitan, Natasya Angel Elizabeth (Asosiasi Dosen Akuntansi Indonesia, 2025)
Knowing the effect of Liquidity ratios on PT's financial performance. GarudaFood Putra Putri Jaya Tbk is the aim of this research. Quantitative Descriptive was used as a method in this research. The sample for this research is the financial report of PT. GarudaFood is in the form of data obtained through the annual report on the GarudaFood website for five years (2019-2023). The hypothesis testing used is multiple linear regression, namely Simultaneous Test and Partial Test. The research results obtained partially show that the Liquidity Ratio (Current Ratio) does not have a significant effect on Financial Performance (ROA) and the Liquidity Ratio (Quick Ratio) does not have a significant effect on Financial Performance (ROA). Simultaneously, the Current Ratio and Quick Ratio influence Financial Performance (ROA). The total coefficient of determination (R. Square) of 0.550 states that the two variables influence ROA of 55%, while 45% is influenced by variables outside the research.